Active disturbance rejection control of three-phase grid-connected photovoltaic systems. (18th March 2020) - Li, Hezheng; Bai, Jing; Kanae, Shunshoku; Li, Yanxi; Yue, Lin
In this paper, a three-phase grid-connected photovoltaic system based on active disturbance rejection controller (ADRC) is proposed to solve the problem of voltage instability which is caused by many internal uncertainties and external disturbances. A tracking differentiator is used to arrange the transient process to reduce the initial error, which solves the problem of large overshoot. The extended state observer is used to estimate the internal and external total disturbances in real-time, and adopts a linearisation technique via dynamic compensation process, which can reject internal and external disturbances effectively. The simulation experiments show that ADRC has better performance than PI controller in reducing power loss and rejecting disturbances.